Enhancement of the second harmonic signal of nonlinear crystals by a single metal nanoantenna. Issue 45 (12th November 2020) - Gürdal, Emre; Horneber, Anke; Meixner, Alfred J.; Kern, Dieter P.; Zhang, Dai; Fleischer, Monika
Abstract : This work fundamentally investigates how the second harmonic generation (SHG) from commercial nonlinear crystals can be boosted by the addition of individual optical nanoantennas. Abstract : This work fundamentally investigates how the second harmonic generation (SHG) from commercial nonlinear crystals can be boosted by the addition of individual optical nanoantennas. Frequency conversion plays an important role in modern non-linear optics, and nonlinear crystals have become a widely used building block for non-linear processes. Still, SHG remains hampered by limited conversion efficiency. To strengthen SHG from the crystal surface, we investigate the interaction of LiNbO3 crystals with individual gold nanodiscs. The scattered intensities and resonance frequencies of the nanodiscs are analyzed by dark-field spectroscopy and simulations. Subsequently, the discs on LiNbO3 are excited by a pulsed femtosecond laser in a parabolic mirror setup. Comparing the SHG at the position of a single nanodisc at resonance on the crystal with that of the unstructured crystal and of gold nanodiscs on a reference substrate, local SHG enhancement of up to a factor of three was achieved in the focal volume through the presence of the antenna.